2011
DOI: 10.1007/s10943-011-9454-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Religiosity on the Quality of Life and on Pain Intensity in Chronic Pancreatitis Patients After Neurolytic Celiac Plexus Block: Case-Controlled Study

Abstract: The quality of life in patients with chronic pancreatitis (CP) is reduced due to their suffering of high levels of pain. It has been presented that quality of life can also be linked to religiosity and/or spirituality. The aim of this study is to assess the influence of religious practices on the quality of life and on the subjective level of pain in CP patients. Ninety-two patients (37 women and 55 men) with chronic pancreatitis were treated invasively for pain with neurolytic celiac plexus block (NCPB). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…As the experience of pain is a subjective phenomenon, the affective and cognitive filtering of pain likely matters more than measureable nociceptive and neuropathic intensity in relationship to levels of hope. 37,38 This study buttresses the notion forwarded by other researchers that patients may maintain a sense of hope even while cancer pain and other symptoms progress, as a function of cognitive-affective and psycho-spiritual resources and resiliency. 39 On a practical note, this study suggests that when confronted with a patient who seems to have ''lost hope,'' the physician should look beyond pain measures and explore psychological adjustment and spiritual concerns.…”
Section: Discussionsupporting
confidence: 72%
“…As the experience of pain is a subjective phenomenon, the affective and cognitive filtering of pain likely matters more than measureable nociceptive and neuropathic intensity in relationship to levels of hope. 37,38 This study buttresses the notion forwarded by other researchers that patients may maintain a sense of hope even while cancer pain and other symptoms progress, as a function of cognitive-affective and psycho-spiritual resources and resiliency. 39 On a practical note, this study suggests that when confronted with a patient who seems to have ''lost hope,'' the physician should look beyond pain measures and explore psychological adjustment and spiritual concerns.…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with our findings, previous research has shown higher levels of prayer–coping predict persistent pain (Alschuler, Molton, Jensen, & Riddle, 2013; Basinski, Stefaniak, Stadnyk, Sheikh, & Vingerhoets, 2013; Crisson & Keefe, 1988), whereas other studies of back pain populations have found no significant correlations between prayer and pain (Keefe, Crisson, Urban, & Williams, 1990; Woby, Watson, Roach, & Urmston, 2005). Shuster, McCormack, Pillai Riddell, and Toplak (2009) hypothesized that prayer, as a passive coping strategy, is more common in those with an external locus of control whereby the individual feels more dependent upon an “other” to decrease pain rather than engaging in active pain management.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, patients with severe physical illnesses such as AIDS, cardiovascular disease, physical disability, cancer, and dialysis coped better with their condition when they report being religious [14,15]. Research supports that longer illness survival rates, lower mortality rates, and improved quality of life often occur among patients with high religiosity [18].…”
mentioning
confidence: 99%